Active commuting to school in Finland, the potential for physical activity increase in different seasons. Issue 1 (1st January 2016) - Kallio, Jouni; Turpeinen, Salla; Hakonen, Harto; Tammelin, Tuija
Abstract : Background: Active commuting to school (ACS) can be a significant source of physical activity and provide many health benefits. Objective: This study identified the potential to increase physical activity levels by promoting ACS in Finnish schools and evaluated the effects of season, distance and age on ACS. Design: Data were collected with a questionnaire from 5, 107 students, aged 10–16, in 45 comprehensive schools in Finland. The distance and the mode of transport to school in different seasons were self-reported. Results: The prevalence of ACS was over 80% during spring/fall for those living 0–5 km from school. ACS was inversely associated with the distance to school and was lower in winter compared to spring and fall. Cycling is less common in winter, especially among girls and younger students. The potential for increasing students' physical activity levels via ACS seems to be largest in winter, especially among students living 1–5 km from school. The variation in the prevalence of ACS between schools was large, especially in winter. Conclusions: When planning interventions to promote ACS, one is encouraged to acknowledge and evaluate the potential in the selected target schools in different seasons. The potential varies largely between schools and seasons and is highly dependent on students' commuting distances.